2006
DOI: 10.1093/bja/ael048
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for treatment of catheter related bladder discomfort: a prospective, randomized, placebo controlled and double blind study

Abstract: I.V. ketamine (250 microg kg(-1)) is an effective treatment for reducing the incidence and severity of postoperative CRBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 6 publications
(9 reference statements)
4
94
3
4
Order By: Relevance
“…Although there has been no validation of NRS for CRBD, NRS is a well-validated tool for assessment of both acute and chronic pain along with the visual analog scale 15 and has also used for assessment of 'unpleasant' feeling and in many CRBD studies. 6,[8][9][10] Butylscopolamine is known to have few, minor adverse effects related to its anticholinergic property; thus, it is generally regarded as a safe drug. 12 In our study, the incidence of anticholinergic adverse effects, such as dry mouth, flushing, and blurred vision, were not increased after butylscopolamine injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been no validation of NRS for CRBD, NRS is a well-validated tool for assessment of both acute and chronic pain along with the visual analog scale 15 and has also used for assessment of 'unpleasant' feeling and in many CRBD studies. 6,[8][9][10] Butylscopolamine is known to have few, minor adverse effects related to its anticholinergic property; thus, it is generally regarded as a safe drug. 12 In our study, the incidence of anticholinergic adverse effects, such as dry mouth, flushing, and blurred vision, were not increased after butylscopolamine injection.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, tolterodine, gabapentin, tramadol, ketamine, and oxybutynin showed preventive effects against CRBD, 1,4-8 but adverse anticholinergic effects were sometimes observed. Tramadol and ketamine increased sedation, 1,5,9 and tolterodine and oxybutynin induced dry mouth. 6,7 In these previous studies, the use of these agents was confined to patients who underwent urologic operations.…”
mentioning
confidence: 92%
“…17 In previous studies, various agents with antimuscarinic properties, such as gabapentin, oxybutynin, tolterodine, and tramadol, were found to reduce the incidence and severity of postoperative CRBD. 1,2,[7][8][9][18][19][20] In this study, use of sevoflurane resulted in a greater reduction in the incidence of CRBD when compared with desflurane by 24%, 33%, and 26% at zero, one, and six hours after surgery, respectively. This preventive effect of sevoflurane on CRBD is similar to that of antimuscarinic agents reported in previous studies in which tolterodine and gabapentin reduced the incidence of CRBD by 19-30% until six hours postoperatively.…”
Section: Discussionmentioning
confidence: 56%
“…1,18 The use of antimuscarinic agents for the treatment of CRBD increased the incidence of postoperative side effects, including dry mouth, nausea, vomiting, and sedation. 1,7,8,18,19 For example, the use of antimuscarinic agents tolterodine and oxybutynin increased the incidence of dry mouth (59%), while the use of tramadol increased the incidences of sedation (92%), nausea (56%), and vomiting (40%). 1,8,19 In this study, the incidences of dry mouth, nausea, and vomiting were within 10% in both the sevoflurane and desflurane groups during the entire study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation